Social aspects of tax policy - Ilimzhanova, Z. A. (Journal of Economic Research & Business Administration, 2016)
A social tax is the important link of economic mutual relations be tween the state and working population. Evolution of social tax and social withholdings for the last 12 years in our country resulted in the real de cline on business. Moreover, as the basis of evolutions are considered the regulative and simulative functions of tax, in spite of the fact that there are enough instruments of tax administration in current tax legislation. It is related to the specific of mutual relations of employer and worker, influences on them except the substantive corresponding provisions of the Tax Code and norms of Labour and Civil Codes. The basic task of social tax administration and social withholdings is the legalization of payments to the workers and, certainly, more consider able height of revenues to the budget of this tax, because it must become financial basis for realization of social politics, including public welfare and social defence of population.